COMPARISON OF THE IMPLEMENTATION OF THE EXCLUSIVE BREASTFEEDING PROGRAM IN THE WORKING AREA OF KUTA ALAM HEALTH CENTER AND LAMPULO HEALTH CENTER, KUTA ALAM DISTRICT, BANDA ACEH CITY - Arafani, Vilda; Fahdhienie, Farrah; Amin, Fauzi Ali (Jukema (Jurnal Kesehatan Masyarakat Aceh), 2024)
Background: Exclusive breastfeeding coverage worldwide is only around 36% during the period 2007-2014. Exclusive breastfeeding coverage at the Lampulo Health Center reached 57.43% higher than the Kuta Alam Health Center at 46.60%. The purpose of this study was to compare the implementation of the Exclusive Breastfeeding Program at the Kuta Alam Health Center with the Lampulo Health Center in 2019. Method: This study is descriptive analytical with a cross-sectional design. The population in this study were all cadres at the Kuta Alam Health Center and the Lampulo Health Center. The sampling technique in this study was by total sampling. Data analysis used the x difference test with the Independent Sample t-test module. Result: The results of this study indicate that the Lampulo Health Center is relatively better than the Kuta Alam Health Center in terms of implementing the Exclusive Breastfeeding program in the aspects of personnel (p value: 0.004), costs or budgets (p value: 0.148), availability of tools/materials (p value: 0.718), and methods in implementing the exclusive breastfeeding program (p value: 0.003). Recommendation: It is expected that the Head of Kuta Alam Health Center and Lampulo Health Center can improve the program of counseling and socialization of Exclusive Breastfeeding with the support of the availability of more qualified implementing personnel, sufficient and well-planned budget and with better quality tools and methods.